None of this is true : a novel [compact disc, unabridged] - Jewell, Lisa (Simon & Schuster Audio, 2023)
Celebrating her forty-fifth birthday at her local pub, popular podcaster Alix Summers crosses paths with an unassuming woman called Josie Fair. Josie, it turns out, is also celebrating her forty-fifth birthday. They are, in fact, birthday twins. A few days later, Alix and Josie bump into each other again, this time outside Alix's children's school. Josie has been listening to Alix's podcasts and thinks she might be an interesting subject for her series. She is, she tells Alix, on the cusp of great changes in her life. Josie's life appears to be strange and complicated, and although Alix finds her unsettling, she can't quite resist the temptation to keep making the podcast. Slowly she starts to realise that Josie has been hiding some very dark secrets, and before she knows it, Josie has inveigled her way into Alix's life, and into her home. But, as quickly as she arrived, Josie disappears. Only then does Alix discover that Josie has left a terrible and terrifying legacy in her wake, and that Alix has become the subject of her own true crime podcast, with her life and her family's lives under mortal threat. Who is Josie Fair? And what has she done?